2004
DOI: 10.1088/0953-4075/38/1/010
|View full text |Cite
|
Sign up to set email alerts
|

Resonance multiphoton ionization and dissociation of dimethyl ether via the and states

Abstract: The three-photon resonance four-photon ionization and dissociation spectra of dimethyl ether (DME) are presented in the wavelength range 450–550 nm at 1 nm intervals. The (3+1) REMPI spectra show three prominent bands corresponding to the and transitions with origins at 61 457 cm−1 (7.615 eV), 59 055 cm−1 (7.322 eV) and 58 010 cm−1 (7.194 eV), respectively. Several ionized species, CH3+, CHnO+ (n = 1–3) and CH3OCH3+, are observed in the region of wavelengths studied here. In order to compare the results, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…2, it can be seen that multiply charged ions of C q+ (q = 2-4) and O q+ (q = 2-4) were observed and some fragment ions of diethyl ether such as C 2 H þ 5 , CH 3 O + , C 2 H 5 O + and C 4 H 9 O + were also recorded. The formation of fragment ions of diethyl ether from MPI has been discussed previously [13][14][15]. In this text, only the formation mechanisms of multiply charged ions of C q+ (q = 2-4) and O q+ (q = 2-4) are investigated and discussed in details.…”
Section: Results and Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…2, it can be seen that multiply charged ions of C q+ (q = 2-4) and O q+ (q = 2-4) were observed and some fragment ions of diethyl ether such as C 2 H þ 5 , CH 3 O + , C 2 H 5 O + and C 4 H 9 O + were also recorded. The formation of fragment ions of diethyl ether from MPI has been discussed previously [13][14][15]. In this text, only the formation mechanisms of multiply charged ions of C q+ (q = 2-4) and O q+ (q = 2-4) are investigated and discussed in details.…”
Section: Results and Analysismentioning
confidence: 97%
“…Dimethyl and diethyl ether are typical organic molecules to investigate the ionization and dissociation dynamics [13][14][15]. For example, Zhu et al [13] investigated the fragmentation of dimethyl ether (DME) in intense femtosecond laser field 810, 405 and 270 nm and proposed there were different dissociation channel at different wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethyl ether (CH 3 OCH 3 ) is the simplest molecule containing the ether functional group, and as a result, understanding the chemistry of this species is useful for building an understanding of the chemistry of larger homologous ether molecules. Additionally, the decomposition chemistry of cationic dimethyl ether has been well characterized by various ionization and mass spectrometric techniques and with complementary theory investigating decomposition. Comparison with such analyses allows us to further evaluate our electron bombardment matrix isolation infrared studies as a complementary technique to decomposition chemistry observed through mass spectrometric analysis.…”
Section: Introductionmentioning
confidence: 99%